FLAVORS OF CHILDHOOD: PROMOTING HEALTHY EATING IN EARLY CHILDHOOD EDUCATION - Bento, Arthur Haruki Kubo; Oliveira, Bianca Sousa; Silva, Matheus Willian Duarte; Soares, Rayssa Aragão; Melo, Renan Saldanha de Oliveira; Oliveira, Sara Ramos; Lima, Vitor Gaspio Freire Carmo; Souza, Yan Oliveira; Marcelino, Ylanna Rodrigues; Guerra, Heloísa Silva (Seven Editora, 2024)
Healthy eating is one of the most powerful practices in the context of health promotion, being one of the pillars for good child development, with a strong impact on adult life. This report deals with the experience of medical students in a health education activity aimed at children on the theme of healthy eating. The experience took place in the context of a municipal center for early childhood education with children from one to three years old. The students used tools such as games and games to provide guidance on healthy eating in a dynamic and interactive way. The action allowed the involvement between academics, children, health professionals and the school community, providing learning in a playful way and allowing academics to act in a real practice scenario, reinforcing essential principles of primary care and the Unified Health System. DOI: https://doi.org/10.56238/sevened2024.037-115